The Values ​​of Local Wisdom in Fostering Teacher’s Social Competency At Al-Hilal Islamic Junior Secondary School (MTs) in Tehoru Village, Central Maluku District - Hasanah, Nur (International Research-Based Education Journal, 2019)
This study aims to analyze and describe the development of teacher’s social competency based on local wisdom at Al-Hilal Islamic Junior Secondary School in Tehoru Village. The values of local wisdom community in Central Maluku district was integrated in the development of teacher social competence. This study employed the qualitative approach. The data source consisted of primary and secondary data. The data were collected through observation, interview and documentation. The data were analyzed using interactive model of Miles and Huberman.The focuses of this study were: (1) the values of local community wisdom, (2) the integration of the local wisdom values in the development of teacher’s social competence, (3) supporting and inhibiting factors in the development of teacher-based social competence of local wisdom. The study reveals three findings. First, the local wisdom value of the people of Central Maluku is Hidop orang basudara which has philosophical value of ale rasa beta rasa, sagu salempeng pata dua, potong di kuku rasa di daging. The values are implemented in societal life like ;masohi, badati, maano. There are also some belief symbols which is convinced by the society like batu kramat. Second, the values of local wisdom in the development of teacher social competence at Al-Hilal Islamic Junior Secondary School in Tehoru village refer to the values of social attitudes and social systems. The social attitudes are brotherhood, responsibility, mutual caring, and cooperation. Whereas the social system is every activity carried out together. Third, there are three inhibiting factors in the development of teacher social competence: the lack of human resources (HR), both educators and educational staff; lack of facilities and infrastructure, and limited of information. In contrast, there is a supporting factor in the development of teacher social competence, namely: the role of community to have active participation regarding the progress of education quality.Keywords: local wisdom, teacher’s social competence